PRIORITY NEEDS FOR DEVELOPING ACADEMIC MANAGEMENT OF TRIAMUDOMSUKSA PATTANAKARN SCHOOL BASED ON THE CONCEPT OF MEANINGFUL LEARNING - Passaman, Nutcha; Charoenkul, Nantarat (Journal of Educational Review Faculty of Education in MCU, 2025)
This research article aimed to: 1) study the current and desired conditions of academic administration at Triamudomsuksa Pattanakarn School based on the concept of meaningful learning, and 2) examine the priority needs for developing academic administration of Triamudomsuksa Pattanakarn School according to the concept of meaningful learning. This study employed a survey research design. The population was Triamudomsuksa Pattanakarn School, under the Secondary Educational Service Area Office Bangkok 2. The key informants included 5 administrators selected by purposive sampling and 125 teachers selected through simple random sampling. The research instrument was a 5-point Likert scaled questionnaire with a reliability coefficient of .973. The data were analyzed using descriptive statistics, including mean and standard deviation, and the Modified Priority Needs Index PNIModified). The research findings revealed as follows: 1) The overall current condition of academic administration was at a moderate level. Among the three aspects, the assessment and evaluation aspect had the highest mean, followed by the learning management aspect, and the curriculum development aspect with the lowest mean. The overall desired condition was at the highest level. The curriculum development aspect had the highest mean, followed by the learning management aspect, and the assessment and evaluation aspect with the lowest mean. 2) The overall needs for academic administration development based on the concept of meaningful learning had a Modified Priority Needs Index (PNIModified) of .384. By aspect, the curriculum development aspect had the highest priority need PNIModified = .394), followed by the learning management aspect (PNIModified = .387), and the assessment and evaluation aspect with the lowest priority need (PNIModified = .371).